2013
DOI: 10.1007/s12094-013-1038-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of prophylactic central neck dissection for papillary thyroid carcinoma

Abstract: PurposeThe need of prophylactic central neck dissection (PCND) in patients with papillary thyroid carcinoma (PTC) is still controversial. The major restriction of PCND is the potential complications. We undertook a retrospective study to discuss its necessity in PTC patients.MethodsA total of 188 patients with PTC who underwent total thyroidectomy and PCND were involved. In all of these, central lymph nodes were pathologic examined. Univariate and multivariate analyses were performed based on tumor location an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 27 publications
(27 reference statements)
2
41
1
Order By: Relevance
“…One of these 2 studies [9] did not consider the presence of lymph nodes in the surgical specimens, and the other one [5] found a similar incidence of hypocalcemia. Although our study cohort was short of these data, some authors indicated that central lymph node dissection was not a risk factor for postoperative hypocalcemia [21,22].…”
Section: Discussionmentioning
confidence: 77%
“…One of these 2 studies [9] did not consider the presence of lymph nodes in the surgical specimens, and the other one [5] found a similar incidence of hypocalcemia. Although our study cohort was short of these data, some authors indicated that central lymph node dissection was not a risk factor for postoperative hypocalcemia [21,22].…”
Section: Discussionmentioning
confidence: 77%
“…Although the lack of these data in our work may be considered a weakness, several authors showed that central neck dissection per se is not a risk factor for postoperative hypocalcemia. [16][17][18][19][20] In summary, our study demonstrates that CT is associated with a significantly lower rate of hypocalcemia than TT. The rate of hypocalcemia was independent of autotransplantation of a parathyroid gland in the TT group.…”
Section: Discussionmentioning
confidence: 84%
“…43 CLN metastasis is considered the most important risk factor for local recurrence. 44 Also it decreases survival and it is related to distant metastasis. 45,46 Bardet et al, stated that the risk of recurrence was low in patients without macroscopic LN involvement; even if pCLND was not applied.…”
Section: Discussionmentioning
confidence: 99%